A systematic literature review on final year capstone project in an engineering curriculum - Rahman, Mizanur; Sarwar, Hasan; Tin, Ting Tin; Kader, MD Abdul (Edelweiss Applied Science and Technology, 2025)
The capstone project course, typically offered in the final year of undergraduate studies, is a key part of engineering education that focuses on hands-on learning. These projects give students the chance to tackle real-world problems using the technical skills and soft skills they have developed during their studies. The main goal is to apply practical engineering methods to solve actual client needs, helping students transition from academic learning to professional practice. This study reviews research on final-year capstone projects from 2015 to 2024 across various engineering subjects. We also note the growing use of capstone projects in non-engineering programs, showing a trend toward experiential learning in higher education. By synthesizing the existing literature, this review highlights the benefits, challenges, and best practices associated with capstone projects. It provides valuable insights for researchers, educators, and curriculum developers who aim to enhance engineering education and improve student outcomes through effective capstone project integration and implementation.